Low Systolic blood pressure as a risk factor for unfavorable outcome from severe injury - Hu, Fan
Objective: To determine the critical value of systolic blood pressure that influences unfavorably the outcome of sever head injury. Design: A retrospective cohort study. Setting: Neosurgical divisions of Huashan and Zhongshan Hospital, both of which are the tertiary teaching hospitals affiliated to Shanghai Medical University. Subjects: Inclusion Criteria: Head injury patients with a GCS (Glasgow Coma Score) of 8 or less occuring on admission or during the preceding 48 hours. Exclusion Criteria: (1) Those with missing information on GCS score, blood pressure, heart rate, arterial blood gas analysis, CT scan diagnosis during the first 6 hoursa after head injury. (2) Those with missing information on age, muli injury, operation, GOS (Glasgow Outcome Scale) score on the day of discharge. 892 patients were included in the study and their charts were reviewed by four trained research assistants. Main Outcome Measure: GOS on day of discharge dichotomized as either "favorable" or unfavorable" for statistical analysis. Data Analysis: Logistic regression model with systolic blood pressure, age, hypoxia, bradycardia, multi-injury, operation, mass on the CT sca/location/ midline shift, osmostic agents, corticosteroids, hypothermia, controlled ventillation, anticonvulsant, barbiturate coma, antibiotic, antihypotensive treatment as independent variables: GOS as dependent variable. Result: Age, SBP multi-injury, infection, bradycardia, mass/midline shift on CT scan, osmotic agents, antihypotensive treatment, controlled ventillation and anticonvulsant treatment were predictors included in the logistic regression model. SBP<90mmHg, as the cut-off level for hypotension showed the better combination sensitivity (76%) and specificity (55.8%) in predicting the unfavorable outcome compared with the other cut-off levels. Conclusion: SBP of ,90 mmHg is the critical value predicting poor outcome of sever head injury.
Theses--(Master in Science in Clinical Medicine-Family Medicine) UPCM
Keywords: Injuries; Blood Pressure